Relationship of an adherence score with blood pressure control status among patients with hypertension and their determinants: Findings from a nationwide blood pressure screening program - Chia, Yook Chin *; Navin Kumar, D.; Ching, S. M.; Ooi, Pei Boon *; Chew, Ming Tsuey *; Chew, B. N.; Mohazmi, M.; Lim, H. M.; Beh, H. C.; Azli, S. O.; Hanis, S. H.; Abdul Hafiz, M. G.; et al. (Wiley, 2021)
This study aimed to examine the relationship of adherence with blood pressure (BP) control and its associated factors in hypertensive patients. This cross‐ sectional nationwide BP screening study was conducted in Malaysia from May to October 2018. Participants with self‐ declared hypertension completed the Hill‐ Bone Compliance to High Blood Pressure Therapy Scale (Hill‐ Bone CHBPTS) which assesses three important domains of patient behavior to hypertension management namely medication taking, appointment keeping and reduced salt intake. Lower scores indicate better compliance while higher scores indicate otherwise. Participant's body mass index and seated BP were measured based on standard measurement protocol. Determinants of adherence to treatment were analyzed using multiple linear regression. Out of 5167 screened subjects, 1705 were known hypertensives. Of these, 927 (54.4%) answered the Hill‐ Bone CHBPTS and were entered into analysis. The mean age was 59.0 ± 13.2 years, 55.6% were female and 42.2% were Malays. The mean Hill‐ Bone CHBPTS score was 20.4 ± 4.4 (range 14‐ 47), and 52.1% had good adherence. The mean systolic BP and diastolic BP were 136.4 ± 17.9 and 80.6 ± 11.6 mmHg, respectively. BP was controlled in 58.3% of those with good adherence compared to 50.2% in those with poor adherence (p = .014). Based on multiple linear regression analysis, female gender (β = −0.72, 95% confidence interval [CI] −1.30, −0.15, p = .014), older age (β = −0.05, 95% CI −0.07, −0.03, p < .001), and individuals with primary or lower educational level (β = −0.91, 95% CI −1.59, −0.23, p = .009) had better adherence to BP management. Interventional programs targeted at the less adherent groups are needed in order to improve their adherence and BP control.